Genetic variants implicated in inflammation and airway remodelling are risk factors for secondary atopic conditions in children and young adults with asthma. (24th May 2012) - Cunningham, J; Cheek, E; Tavendale, R; Mitra, A; MacGregor, D; Palmer, CNA; Smith, HE; Mukhopadhyay, S; Basu, K
Abstract : Introduction: Asthma is one of the most common childhood diseases and has a major impact on quality of life and healthcare costs. Individuals with asthma often suffer from secondary atopic conditions which impact on their day to day life and are risk factors for asthma exacerbations, the predominant morbidity in asthma that represents a major burden on the healthcare system. To identify predictive markers of atopy in children with asthma, participants were recruited into the BREATHE study, a UK wide cross sectional study of gene environment interactions in children and young adults with asthma. Methods: 1539 children and young adults with physician-diagnosed asthma (age 3-22 years) from Sussex, England and Tayside and Dumfries, Scotland agreed to participate between 2004 and 2011. The dataset includes information about demographic, anthropometric and clinical details from 29 primary care practices and 8 secondary care asthma clinics. To investigate the combined risk that these variants present, we developed a variable consisting of 1 or more risk variants versus none. We investigated overall atopy, reported allergy to house dust mite (HDM), to fur, to nuts and seasonal rhinitis. Results: The minor G allele of MMP12rs652438 increases the risk of reported allergy to HDM when compared to the A allele (OR=2.04; 95% CI 1.24–3.35; P=.0005). The merged GST mutant variant increases the risk of overall atopy (OR=1.92; 95% CI 1.30–2.84; P=.001), and the risk of reported allergy to HDM (OR=1.79; 95% CI 1.09–2.95; P=0.022) when compared to the wildtype variant. The merged risk variant increases the risk of overall atopy (OR=3.24; 95% CI 1.60–6.58; P=0.001), and the risk of reported allergy to HDM (OR=2.55; 95% CI 1.08–6.01; P=0.032), to fur (OR=2.20; 95% CI 0.99–4.92; P=0.054) and to seasonal rhinitis (OR=1.83; 95% CI 1.04–3.23; P=.035). Conclusion: We present clinically relevant findings on the impact of genetic variants on atopy. The presented variants increase the risk of reported overall atopy, HDM allergy, fur allergy and seasonal rhinitis in children and young adults with asthma. The study increases our understanding of the role of these molecules in influencing the risk profile of atopic disease. The work could define susceptible population groups among children with asthma and help develop novel, personalised approaches for asthma management, providing economic benefits for an over-stretched healthcare system.